The Effect of Guided Inquiry Learning Model Through the Utilization of School Environment Towards Students' Scientific Literacy on Biodiversity Concepts - Lena Wahyuni; Evi Amelia; Indria Wahyuni (International Journal of Biology Education Towards Sustainable Development, 2022)
This research aimed to observe the effect of guided inquiry learning model through the utilization of school environment toward student scientific literacy on biodiversity concepts. This research  was a quasi-experimental research that using randomized control group, pretest-posttest design. The sampling technique used in this research was simple random sampling at one high school i Serag City, Indonesia with class X MIPA 5 as an experiment class and class X MIPA 4 as control class. The result of the scientific literacy was analyzed used t test on significant level α = 0,05, significance value result was (0,000) 0,05 H0 rejected for competence science and significance value result was (0,004) 0,05 H0 rejected for attitude science. Therefore it can be conclude that there was effect of guided inquiry learning model through the utilization of school enviroment towards students’ scientific literacy on biodiversity concepts.